2012
DOI: 10.1007/s12262-012-0520-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Incision by High Frequency Cautery

Abstract: Traditionally, the knife has been used to make surgical incisions on the skin, but recent data suggest that diathermy blade allows the incision to be made more quickly, with less blood loss, less postoperative pain and no adverse effects on wound healing or cosmetic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Theoretically however, literature exists on thermal stimulation too of neural structures; Plaghki et al having reported stimulation of peripheral nerves using non-noxious radiant heat produced by laser [18]. Literature exists on use of monopolar diathermy for making surgical skin incisions too, without causing any thermal necrosis [1]. None the less, though a concern for thermal injury does exist; no patient in the present study had any evidence of such a complication.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Theoretically however, literature exists on thermal stimulation too of neural structures; Plaghki et al having reported stimulation of peripheral nerves using non-noxious radiant heat produced by laser [18]. Literature exists on use of monopolar diathermy for making surgical skin incisions too, without causing any thermal necrosis [1]. None the less, though a concern for thermal injury does exist; no patient in the present study had any evidence of such a complication.…”
Section: Discussionmentioning
confidence: 60%
“…Surgical diathermy involves the passage of high frequency alternating electric current through body tissues [1]. Diathermy may be either monopolar or bipolar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced incisional blood loss in the diathermy group is in concordance with the findings in a similar study. 11,14,15 There was only a slight difference in volume. The mean blood loss in the diathermy group was 1.53±3.84 ml whilst theirs 11 was 1.43±0.201 ml.…”
Section: Discussionmentioning
confidence: 96%
“…Dear editor, I read the article by Vedbhushan et al with interest; I would like to thank the authors for doing the study [1]. High frequency diathermy has been an important tool to surgeon since use by Harvey Cushing in 1926 [2].…”
mentioning
confidence: 99%